Developmental staging of Banf1 : early embryonic lethality in the mouse with doubly-disrupted gene expression - Ma, Hui Ling (2015)
Barrier-to-Autointegration Factor (BAF) is a 10kDa cytoplasmic/nuclear protein that is encoded by Banf1. BAF exhibits interaction with many key binding partners, with implications in mouse embryonic stem cell development, chromatin reorganization and essential biological gene functions. Homozygous mutation in Banf1 was reported in a non-classical case of progeria (premature aging). A BAF Knock-Out mouse model was generated to study how BAF affects mammalian developmental processes. In this study, BAF is shown to be expressed in all cells of E3.5 stage mouse blastocyst. We found BAF deficiency to cause impairment of inner cell mass growth and expansion in vitro, which is the likely cause of early embryonic lethality at peri-implantation stages. We conclude that BAF is indispensable for early embryonic survival and development.